Isolated pediatric transolecranon fracture‐dislocation of the elbow managed nonoperatively: A case report and review of literature. Issue 7 (17th June 2019) - Arain, Abdul Rehman; Haddad, Stefanos; Anderson, Matthew; Murtaza, Hamza; Rosenbaum, Andrew
Abstract: We report on the sixth case of an isolated pediatric transolecranon fracture‐dislocation, and the first case utilizing nonoperative management in a cast following closed reduction resulting in an excellent outcome. Our case provides support for nonoperative management of these rare injuries, especially when surgery is not practical or desirable. Abstract : We report on the sixth case of an isolated pediatric transolecranon fracture‐dislocation, and the first case utilizing nonoperative management in a cast following closed reduction resulting in an excellent outcome. Our case provides support for nonoperative management of these rare injuries, especially when surgery is not practical or desirable.